Psychological Support System for Hospital Workers During the Covid-19 Outbreak: Rapid Design and Implementation of the Covid-Psy Hotline - Geoffroy, Pierre A.; Le Goanvic, Véronique; Sabbagh, Olivier; Richoux, Charlotte; Weinstein, Aviv; Dufayet, Geoffrey; Lejoyeux, Michel (Frontiers in Psychiatry, 2020)
Background: The world-wide coronavirus outbreak put hospital workers under extreme pressures with possible mental health problems. In this context, we decided to rapidly design and implement a psychological support system for all hospital workers in Paris during the Covid-19 outbreak. Methods: In 3 days we built the hotline with the following steps: 1) official mandate, 2) request for the creation of hotline numbers, 3) formulation of psychological intervention materials and rules, 4) call for volunteer trained psychologists, 5) call for volunteer trained psychiatrists to supervise in case of psychiatric cases, 6) creation of an anonymous and protected database, 7) communication and regular reminders about the existence of the hotline for hospital workers. Results: After the first 26 days, we received 149 calls with a mean of 5.73 calls/day (SD=3.22). The average call duration was 18.5 min (min=1; max=65min; SD=14.7), and mostly women (86%) called. The mean age was 32.7 years old (SD=11.0). Hospital workers calls were from all professions, mostly represented by frontline healthcare givers, but also non-frontline departments (total of 42 departments). Problems were anxiety disorders (n=73, 49%), request for hotline information (n=31, 20.8%), worries about Covid-19 (n=23, 15.44%), exhaustion (n=17, 11.41%), trauma reactivation (n=10, 6.11%), insomnia (n=9, 6.0%), anger (n=8, 5.37%), depression (n=6, 4.02%), and delirium (n=3, 2.01%). Regarding referrals, 105 (70.47%) of them were referred to psychosocial, Covid and general supports. Conclusions: This psychological support system can be easily duplicated, and seem to benefit to all hospital professions that all appeared mentally affected.